External Quality Assessment of Sputum Smear Microscopy in Tuberculosis Laboratories in Sughd, Tajikistan - Eva Chang; Fabio Luelmo; Zamira Baydulloeva; Marija Joncevska; Guljamol Kasymova; Oktam Bobokhojaev; Tom Mohr (University Library System, University of Pittsburgh, 2016)
Introduction: Tajikistan has a laboratory network with three levels of tuberculosis (TB) laboratories. The external quality assessment (EQA) of sputum smear microscopy was implemented in 2007. The objective of this study was to evaluate the EQA system and identify potential performance improvement strategies in TB microscopic laboratories in Sughd, Tajikistan. Methods: This is a cross-sectional study based on retrospective record review and secondary data analyses on Acid-Fast Bacilli (AFB) microscopy data and EQA reading results collected between the first quarter of 2011 and the fourth quarter of 2013. Descriptive analyses were conducted to examine the overview of microscopy laboratories activities, EQA results, and laboratory performance. Result: Of the 123,874 smears examined between 2011 and 2013, 11,522 (9.30%) were re-checked by the EQA system. The population TB screening rate rose from 0.46% in 2011 to 0.57% in 2013, and the case positivity rate decreased from 6.98% to 4.80%. The regional EQA results showed a reduction in high false-positive, high false-negative, and low false-negative errors. False-positive errors had decreased from 0.13% in 2011 to 0.07% in 2013, and false-negative errors from 0.91% in 2011 to 0.15% in 2013. Regional sensitivity of smear microscopy, when compared to re-checking controller, increased from 88.2% in 2011 to 97.2% in 2013. The regional specificity level remained relatively stable at above 99%. Conclusion: Our study found that a decreasing trend of case positivity rate from 2011 to 2013 in Sughd, though the overall laboratory workload was on the rise. In addition, EQA results showed an overall error reduction and an improved sensitivity of smear microscopy in the region. The overview of microscopic laboratory activities and the actual evaluation of the EQA system on sputum smear microscopy complement each other in providing a better picture on the progress of TB laboratory strengthening. We recommend similar approaches to be adapted by future evaluations on TB microscopic laboratories, particularly among countries of high burden. Interactive training and feedback loops are crucial to improving TB surveillance in Tajikistan.